2012
DOI: 10.1097/opx.0b013e31826c5f63
|View full text |Cite
|
Sign up to set email alerts
|

Using Optical Coherence Tomography to Assess Corneoscleral Morphology After Soft Contact Lens Wear

Abstract: In this preliminary study, we have shown that soft contact lenses can produce small but significant changes in the morphology of the limbal/scleral region and that OCT technology is useful in assessing these changes. The clinical significance of these changes is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…In the periphery the changes were bigger, which generally is in agreement with our results. Alonso-Caneiro et al [44] studied with OCT corneoscleral morphology after soft contact-lens wear, but they analyzed several layers of the corneoscleral junction and proximities, which cannot be compared with our results.…”
Section: Discussioncontrasting
confidence: 63%
“…In the periphery the changes were bigger, which generally is in agreement with our results. Alonso-Caneiro et al [44] studied with OCT corneoscleral morphology after soft contact-lens wear, but they analyzed several layers of the corneoscleral junction and proximities, which cannot be compared with our results.…”
Section: Discussioncontrasting
confidence: 63%
“…18,37,45 With the advance in optical coherence tomography imaging techniques, studies 272,273 have revealed high-resolution details of the contact region between the lens and the eye and lens edge fitting. A recent study 274 has shown small but significant changes in the morphology of the limbal/scleral region with soft contact lens wear. In addition to frictional wear, the peripheral corneal topography, lid anatomical features, lens design and rigidity, and surface characteristics are also contributing factors to this mechanical related complication.…”
Section: Mechanicalmentioning
confidence: 97%
“…Staining of the ocular tear film with fluorescein is used to evaluate the RGP contact lens fit and to assess the ocular surface after a period of wear. However, both methods provide limited information on the interaction between the lens and the ocular surface, and this examination may be insufficient to understand the cause of CL-induced discomfort and complications [28][29][30][31].…”
Section: Clinical Uses In CL Practicementioning
confidence: 99%
“…However, the central corneal topography does not correlate with the best fitting curve for a soft CL [28]. Many researchers have assessed the corneoscleral region, reporting that, contrary to usual depictions, it is often smooth and tangential and that its topography is relevant in a CL fitting approach [1,22,24,27,29,33]. Hall et al evaluated the influence of corneoscleral junction topography measured by OCT on soft CL fit and concluded that the architecture of the marginal cornea and perilimbal sclera significantly affects the optimal dynamic CL fitting [27].…”
Section: Qualitative and Quantitative Evaluation: Surface Topography mentioning
confidence: 99%
See 1 more Smart Citation